Współzależności polityczne i gospodarcze między Australią i Japonią po II wojnie światowej - Sprengel, Mieczysław (The political and economic interdependence between Australia and Japan after the Second World War, 2009)
The article presents Crawford’s concept of the relationship between Australia and Japan. Crawford created this concept already before the Second World War. Under the circumstances of careful talks, Crawford’s concept was received as revolutionary by the governing people. Japan’s behaviour during the Second World War did not encourage to develop contact between Australia and Japan, because of Japanese aggression. In spite of that, Australian’s vision of co-operation was affected in two fields: politics and economy. Two political important documents were: - the ANZUS pact, signed on September 1, 1951, - the San Francisco Peace Treaty with Japan, signed on September 8, 1951. The next part of the article presents the gradual process of growing trade between Australia and Japan in the 50s of the 20th century. This process was especially concentrating on Japan. It mostly concentrates on the internal-policy of Australia. The base of this development was the Commercial Agreement of 1957, which is the last point discussed in the article
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67